Pendampingan bahasa Jepang bagi mahasiswa pariwisata berbasis kemitraan industri - Herman Supriadi; Jamaluddin Jamaluddin; Muhammad Ramli; Baiq Desi Dwi Arianti (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Tourism service quality is strongly shaped by communication quality; therefore, foreign-language competence—including Japanese—has become increasingly relevant for tourism students. This community service program aimed to strengthen basic Japanese skills among Tourism students at Universitas Hamzanwadi through an industry-partnership mentoring model with PT Ina Nippon Indonesia. The six-month program (July–December) involved 23 participants (third semester, fifth semester, and alumni) and focused on three foundational literacy components delivered sequentially: Hiragana (July–August), Katakana (September–October), and Kanji (November–December). Learning activities combined structured drills, group discussions, and service-dialog simulations, supported by periodic assessments through written tests and Japanese-led interviews (every three months). Quantitative results from average scores show consistent improvement across all components: Hiragana increased from 49 to 76 (+27 points), Katakana from 50 to 81 (+31 points), and Kanji from 48 to 79 (+31 points). These gains suggest that scheduled, intensive mentoring aligned with tourism-service communication needs is effective in building basic Japanese literacy and supporting students’ functional communication readiness. Future implementation should strengthen the assessment system using detailed scoring rubrics and individual score documentation to provide more robust evidence of program impact and sustainability.